2017
DOI: 10.4172/2168-975x.1000235
|View full text |Cite
|
Sign up to set email alerts
|

The Current Utilization of Cognitive Tests in the Research of Radiation-Induced Cognitive Dysfunction in Rodent Models

Abstract: Recent clinical studies suggest that radiation-induced damage to the hippocampus plays a considerable role in the cognitive dysfunction of patients after cranial irradiation. In particular, deficits in learning, memory, and spatial processing observed in patients who received WBI are thought to be related to hippocampal injury [7]. The mechanisms of radiation-induced cognitive dysfunction are not yet fully understood. According to the available knowledge, radiation-induced cognitive dysfunction is hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…Pre-clinical studies utilizing rodents have demonstrated hippocampal-dependent impairments in multiple behavioral tasks (6) suggesting that the hippocampus is an important target in irradiation-mediated cognitive decline, a result supported by hippocampal sparing radiotherapy strategies (7). The interconnectivity of the hippocampal network depends on the dynamic modification and remodeling of dendritic spines to allow synaptic plasticity and proper allocation of experience-dependent memories (8).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical studies utilizing rodents have demonstrated hippocampal-dependent impairments in multiple behavioral tasks (6) suggesting that the hippocampus is an important target in irradiation-mediated cognitive decline, a result supported by hippocampal sparing radiotherapy strategies (7). The interconnectivity of the hippocampal network depends on the dynamic modification and remodeling of dendritic spines to allow synaptic plasticity and proper allocation of experience-dependent memories (8).…”
Section: Introductionmentioning
confidence: 99%